2018
DOI: 10.3389/fpls.2018.01654
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Sowing and Flooding Depth for Anaerobic Germination-Tolerant Genotypes to Enhance Crop Establishment, Early Growth, and Weed Management in Dry-Seeded Rice (Oryza sativa L.)

Abstract: Poor crop establishment, high weed infestation, and consequent yield loss are major concerns for dry-seeded rice (DSR). Flooding after seeding helps in managing weeds but reduces seed germination and crop stand. Anaerobic germination (AG)-tolerant rice genotypes could overcome these problems in DSR. Screenhouse experiments were established to evaluate the effect of seed sowing depth (SD) (0.5 cm, 1 cm, and 2 cm) and flooding depth (FD) (saturated, 2 cm, and 5 cm) on crop establishment, early growth, and weed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 53 publications
(81 reference statements)
1
18
0
2
Order By: Relevance
“…The final GWAS panel contained mainly indica accessions (329), a smaller number of aus accessions (19), and several admixed accessions (3) (Figure S3; Supplementary File S3), confirming that AG2-related genotypes exist in both sub-groups (MR and KHO are indica, while Nanhi and Kharsu are aus). Interestingly, even though the panel was highly enriched for potential MR-derived AG2 haplotypes, phenotyping revealed that most accessions were not AG tolerant.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The final GWAS panel contained mainly indica accessions (329), a smaller number of aus accessions (19), and several admixed accessions (3) (Figure S3; Supplementary File S3), confirming that AG2-related genotypes exist in both sub-groups (MR and KHO are indica, while Nanhi and Kharsu are aus). Interestingly, even though the panel was highly enriched for potential MR-derived AG2 haplotypes, phenotyping revealed that most accessions were not AG tolerant.…”
Section: Discussionmentioning
confidence: 67%
“…The gene underlying this QTL was cloned as OsTPP7, a trehalose-6-phosphate phosphatase gene, which enhances anaerobic germination tolerance [16]. This QTL has been used for crop improvement and has been successfully validated in the field [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…OsTPP7 is considered to be associated with starch mobilization which drives the growth kinetics of the germinating embryo and elongating the coleoptile under anaerobic conditions. In addition, a near isogenic line of qAG-9-2 showed better seedling establishment under flooding stress compared with the background variety, showing a higher grain yield in the paddy field (Chamara et al, 2018;Lal et al, 2018). In high latitude areas such as in East Asia, seedling emergence were observed under low temperature conditions in addition to flooding stress (Fukuda et al, 2014;Iwata et al, 2010).…”
Section: Introductionmentioning
confidence: 94%
“…Additional efforts to screen more varieties had been conducted at IRRI (E. Septiningsih, unpublished data). Some of these accessions have been used for physiological and agronomical studies, and as donors in genetic studies and crop improvement efforts [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%